Assessing the Key Factors Affecting the Teachers’ Quality of Work Life: Focusing on High School Teachers in the Cambodian Context - Samnang Pann; Sophay Sim; Sophan Near; Satya Yen; Sophany Ty; Sasigaran Moneyam (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
Quality of work life is a core element relating to many factors of teacher performance and educational quality in Cambodia. To improve the quality of education, it is necessary to improve the quality of teachers’ work life, because teachers are the main drivers of educational quality. Given its important, the main purpose of this study was to identify the key factors affecting the quality of work life of Cambodian high school teachers. This study also examines the similarities and differences between the key factors affecting the quality of work life based on the demographic information and analysis the relationship between the variables of those key factors. A cross-sectional quantitative design was utilized, involving a sample total of 760 high school teachers from different demographic characteristics from 3 representative provinces and 1 capital city participated in this study. The instrument used in this study was the set of questionnaires which was adapted and prepared by researcher with its reliability at 0.97. Collected data were analysed using statistical methods such as descriptive statistics, t-test, One-way ANOVA, Pearson correlation, and multiple linear regression. There were many implications for improving quality of work life and while organizational alliance had a strong affecting quality of work life. The findings revealed that, overall, the quality of working life of Cambodian high school teachers was at a high level (M=3.55, SD= 0.55). Ranks from the highest to the lowest mean values were: organizational alliance, job satisfaction, organizational climate, organizational culture, and quality of work life, respectively. Pearson correlation analysis revealed significant positive relationships among all studied factors. However, multiple regression analysis indicated unexpected negative pathways for job satisfaction and organizational alliance when controlling for other variables, suggesting complex context-specific dynamics. These baseline insights offer critical implications for educational policymakers seeking to refine teacher-centric support frameworks and institutional environments in Cambodia.